Challenges facing emergency departments in public hospitals - Alshareef, Abdullah Ghaleb (Edelweiss Applied Science and Technology, 2025)
The management of hospitals are facing increasing challenges in managing the service and quality of the emergency department. This study identifies the challenges faced by healthcare professionals who work in the emergency department and identifies practical solutions to enhance the sustainable management and leadership of the emergency department. A qualitative study was conducted with health professionals who work in the emergency department in three public hospitals in Saudi Arabia, including six managers, five physicians and seven nurses. Data were collected through one-on-one interviews from purposively selected the emergency department at public hospitals in Saudi Arabia. Three themes emerged from interviews that described the challenges and experiences of health professionals: ethical dimensions, management dimensions, and health system dimensions. The results of the current study indicate that patient overcrowding, long waiting hours in emergency departments, having to make decisions concerning which patients to treat first and the quality of services, leadership and team effectiveness were major contributors to the struggles faced by health professionals inside the emergency department. This study provides the most comprehensive information available to date about the challenges faced by the emergency department managers and leadership and provides suggestions to develop short and long-term strategies to reduce overcrowding in hospitals.